Single-atom Ru catalyst for selective synthesis of 3-pentanone via ethylene hydroformylation. Issue 22 (28th October 2021) - Qin, Tingting; Dang, Yaru; Lin, Tiejun; Mei, Bingbao; Wu, Bo; Li, Xiao; Li, Shenggang; Jiang, Zheng; Tang, Zhiyong; Zhong, Liangshu; Sun, Yuhan
Abstract : A Ru single-atom (Ru SA) catalyst supported on activated carbon was adopted to synthesize 3-pentanone with 83.3% selectivity via heterogeneous ethylene hydroformylation, while 52.1% ethane selectivity was obtained for Ru nanoparticles (Ru NPs). Abstract : A Ru single-atom (Ru SA) catalyst supported on activated carbon was adopted to synthesize 3-pentanone with 83.3% selectivity via heterogeneous ethylene hydroformylation, while 52.1% ethane selectivity was obtained for Ru nanoparticles (Ru NPs). The atomically dispersed Ru species with oxidation state (Ru δ + ) and Ru-C4O coordination structure were identified as the active sites for efficient C–C coupling to generate 3-pentanone, while metallic Ru nanoparticles exhibited high activity for ethylene hydrogenation to ethane. Density functional theory (DFT) calculation revealed that the energy barrier of the direct coupling of C2 H5 CO* with C2 H5 * to form 3-pentanone on Ru SA was much lower than that on Ru NPs. As a result, the formation of 3-pentanone over Ru SA was more favourable than propanal, which was admittedly generated via coupling of C2 H5 CO* and H*. This strategy may provide a potential green route for the one-pot synthesis of 3-pentanone with high atomic economy.